Implicit and incremental computation of primes and essential primes of Boolean functions - Coudert, O.; Madre, J.C. ([1992] Proceedings 29th ACM/IEEE Design Automation Conference, 1992)
Recently introduced implicit set manipulation techniques have made it possible to formally verify finite state machines with state graphs too large to be built. The authors show that these techniques can also be used with success to compute and manipulate implicitly large sets of prime and of essential prime implicants of incompletely specified Boolean functions. These sets are denoted by meta-products that are represented with binary decision diagrams (BDDs). Two procedures are described. The first is based on the standard BDD operators, and the second, more efficient, takes advantage of the structural properties of BDDs and of meta-products to handle a larger class of functions than the first procedure.< >